(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2020)
Professor Bidyut Kanti Datta, a renowned professor of the Department of Pharmacy, Faculty of Pharmacy, University of Dhaka, died at the age of 73 on Friday 11 September 2020 in Canada (Canadian time 7.10 am and BD time 5.10 pm), as a consequence of COVID-19 infection followed by pneumonia. This article is a brief review of his research work where the authors of this article are immensely proud to be associated with. Prof Datta published more than 60 research articles in reputed journals, and the lead author (SDS) of this article, one of his former students from the University of Dhaka, is a co-author of 20 of those publications. These 20 publications resulted from a long-standing research collaboration that spanned over two decades, especially research involving various Bangladeshi species of the genus Polygonum L. of the family, Polygonaceae, and they demonstrate the breadth and depth of research activities that Prof Datta was involved in, and his long-standing commitment to research that underpinned and enriched his teaching offerings to hundreds of students he taught in higher education sector in Bangladesh. Dhaka Univ. J. Pharm. Sci. 19(2): 97-103, 2020 (December)